Influence of secondary dendrite arm spacing (SDAS) on the fatigue properties of different conventional automotive aluminum cast alloys (Fracture and Structural Integrity, 2019)
For industrial in-series castings, the presence of casting defects, like porosity, geometrically complex intermetallic precipitates and the occurrence of eutectic silicon of varying morphologies, is well known but hard to prevent due to technical and economic limitations. To improve the performance and safety of cast aluminum products, the present work deals with the correlation between the cooling-rate-dependent secondary dendrite arm spacing (SDAS), the high- and very-high-cycle-fatigue (VHCF) behavior, the crack propagation mechanisms under pure bending with a focus on the crack propagation paths for near-threshold stress intensity factor ranges ∆KI using two conventional automotive cast aluminum alloys AlSi8Cu3 (engine blocks) and AlSi7Cu0.5Mg (cylinder heads). Furthermore, the role of a variation in porosity on the crack initiation process is discussed. Specimens were extracted from in-series castings choosing positions with a maximal difference in cooling rate and SDAS, respectively. It is shown that porosity is highly influencing the crack initiation mechanism and that the SDAS has a strong influence on both, crack propagation rate and crack propagation paths. Hence, analogies between the SDAS and the grain size as influence factor according to the Hall-Petch relationship were identified.
Keywords: Cast; Aluminum; SDAS; Threshold; Kitagawa-Takahashi-Diagram; Hall-Petch-Relationship